Tissue specific diversification, virulence and immune response to Mycobacterium bovis BCG in a patient with an IFN-γ R1 deficiency - Cecilia B. Korol (Taylor & Francis Group, 2020)
Summary: We characterized Mycobacterium bovis BCG isolates found in lung and brain samples from a previously vaccinated patient with IFNγR1 deficiency. The isolates collected displayed distinct genomic and phenotypic features consistent with host adaptation and associated changes in antibiotic susceptibility and virulence traits. Background: We report a case of a patient with partial recessive IFNγR1 deficiency who developed disseminated BCG infection after neonatal vaccination (BCG-vaccine). Distinct M. bovis BCG-vaccine derived clinical strains were recovered from the patient’s lungs and brain. Methods: BCG strains were phenotypically (growth, antibiotic susceptibility, lipid) and genetically (whole genome sequencing) characterized. Mycobacteria cell infection models were used to assess apoptosis, necrosis, cytokine release, autophagy, and JAK-STAT signaling. Results: Clinical isolates BCG-brain and BCG-lung showed distinct Rv0667 rpoB mutations conferring high- and low-level rifampin resistance; the latter displayed clofazimine resistance through Rv0678 gene (MarR-like transcriptional regulator) mutations. BCG-brain and BCG-lung showed mutations in fadA2, fadE5, and mymA operon genes, respectively. Lipid profiles revealed reduced levels of PDIM in BCG-brain and BCG-lung and increased TAGs and Mycolic acid components in BCG-lung, compared to parent BCG-vaccine. In vitro infected cells showed that the BCG-lung induced a higher cytokine release, necrosis, and cell-associated bacterial load effect when compared to BCG-brain; conversely, both strains inhibited apoptosis and altered JAK-STAT signaling. Conclusions: During a chronic-disseminated BCG infection, BCG strains can evolve independently at different sites likely due to particular microenvironment features leading to differential antibiotic resistance, virulence traits resulting in dissimilar responses in different host tissues.